Efektivitas penerapan manajemen risiko pembiayaan pada produk perbankan syariah di Indonesia - Sahira, Firzanah (Maliki Interdisciplinary Journal, 2025)
This study analyzes the effectiveness of financing risk management in Indonesian Islamic banking, which is unique because its sharia contracts (Murabahah, Mudharabah, Musyarakah) are based on profit sharing and partnership. Risk management includes the identification, measurement, and mitigation of risks such as credit, operations, and sharia compliance. In sharia financing risk management, it must be adjusted to the characteristics of the contract. Mudharabah, Musharakah, and Murabahah contracts have specific risks that require different mitigation strategies. An incentive-based approach, feasibility analysis, transparency, and supervision are the keys to the effectiveness of risk management according to sharia principles. The effectiveness of the application of risk management in NPFs includes the 5C Method of Character, Capacity, Capital, Collateral, and Condition), the process of revitalization and renegotiation of the contract (remedial). Challenges include limitations in human resources, technology and data quality and increasing NPF. Increasing the effectiveness of risk management of sharia financing requires strategies based on sharia principles, such as human resource training, the use of fintech and big data, the maqasid al-shariah approach, and the handling of NPF based on restructuring and deliberation. This measure ensures a balance between financial sustainability and sharia compliance.